Correction : Development of Regression Model for Predicting the Maximum Static Friction Force of Tractors with a Front-End Loader - Kim, Seung-Jun; Gim, Dong-Hyeon; Jang, Moon-Kyeong; Hwang, Seok-Joon; Kim, Jeong-Hun; Yang, Yun-Jeong; Nam, Ju-Seok (Journal of Biosystems Engineering, 49(1), 2024)
KCI Citation Count: 0